Seismic response mitigation of a wind turbine tower using a tuned parallel inerter mass system - Zhang, Ruifu; Zhao, Zhipeng; Dai, Kaoshan (Engineering structures, 2019)
•TPIMS was proposed as a lightweight device to reduce wind turbine tower vibrations.•An optimum design method was developed to minimize tuned mass weight of TPIMS.•TPIMS shows robustness and is superior to TMD in the aspect of additional mass. Traditional tuned mass dampers have been studied to reduce vibration responses of wind turbine towers. However, the large additional mass is usually required to be installed at the top of the tower, which may be not suitable for existing wind turbine tower. To provide a retrofit technology for in-service wind turbines, the use of a lightweight energy dissipation device, the tuned parallel inerter mass system (TPIMS), for seismic response mitigation of the wind turbine tower, was proposed in this study. The TPIMS consists of a tuned mass, a spring, and a parallel inerter subsystem, of which the spring is used for tuning the mass and the inerter subsystem is set for vibration energy absorbing and dissipation. A TPIMS-design optimization method was developed for wind turbine tower vibration depression with a target performance level. A typical wind turbine tower was modeled according to the Bernoulli-Euler beam theory and its seismic responses subject to stochastic seismic excitations were obtained. Parametric studies were conducted and the robustness of TPIMS for tower seismic vibration mitigation was proved. The results show that the tower top displacement, base shear, and moment can be reduced significantly with the help of TPIMS. Under a same design target, the required physical mass of TPIMS is much smaller than that of the tuned mass damper. Additionally, a lager apparent mass of TPIMS is more effective for reducing seismic responses of the wind turbine tower.